The Community press and its revolutionary tradition - Encanto, Georgina Reyes (Quezon City, Philippines : UP Press, 2019)
The narrative of the Philippines as a nation built by struggles for freedom, in which free speech and Press freedom are integral, has often overlooked the contribution of small, sometimes ephemeral, but often vocal publications that Georgina Reyes Encanto has termed the "community press".
The Rise of Provincial Press -- Factors that contributed to the rise of the Provincial Press in the 1880s -- The Pioneer Provincial Newspapers -- Folklore and Journalism: A Nascent Form of Nationalism -- The Community Press during the American Regime as an Instrument for Resistance and Campaign for Independence -- The Guerrilla Press: The Site of Underground Resistance during the Japanese Occupation from 1941 to 1945 -- The Post-war Community Press -- The Provincial Press during the Martial Law Years (1972-1986) -- The Alternative or Mosquito Press -- The Provincial Press and its Continuing Resistance -- The Religious Press: The First Bastion of Resistance -- The Campus Press: A Vibrant Hub of Continuing Dissent -- The Underground Press -- The Community Press since 1986: The Decline if the Revolutionary Tradition -- The Killing of Journalists and the culture of Impunity -- Conclusion.
Includes bibliographical references and index.
Keywords: PRESS -- PHILIPPINES -- HISTORY